Fecal Calprotectin Level of Breast Milk-Formula vs Formula Feeding in Preterm and Low Birth Weight Neonates with Necrotizing Enterocolitis - Arisanti, Ditya; Wibowo, Satrio (Journal of Tropical Life Science, 2019)
Necrotizing enterocolitis (NE) is inflammatory disease and its prevalence was increase in preterm and low birth weight (LBW) neonates. This study was aimed to investigate the differences of fecal calprotectin level in breast milk-formula vs formula feeding infants in preterm and low birth weight neonates with necrotizing enterocolitis. There are 32 preterm and LBW neonates with NE were divided into two group (breast milk-formula and formula only feeding group). Fecal calprotectin level was measured using ELISA method. This study showed that fecal calprotectin level in breast milk-formula feeding group was insignificantly lower as compared to formula feeding group (independent t-test, p = 0.503). Further analysis showed that fecal calprotectin level was negatively correlated with patient’s outcome (Spearman correlation test, p = 0.03, r = 0.512). We concluded that fecal calprotectin level in breast milk-formula feeding group was insignificantly lower as compared to formula feeding only group in preterm and low birth weight neonates diagnosed with necrotizing enterocolitis. There was negative correlation between fecal calprotectin level and patient’s outcome.